Generating DNA profile from low copy number DNA: Strategies and associated risks - Rana Muhammad Mateen; Asma Tariq; Mureed Hussain (Acta Scientiarum. Biological Sciences, 2020)
Many shreds of evidence found on the crime scenes contain a trace amount of DNA which results in insignificant profiling results for subsequent comparison. This can nullify the potential evidence material and hamper investigation process. Over the years, different strategies have been employed by various DNA testing laboratories to create interpretable DNA profiles generated from low template of DNA. This review highlights different strategies used by forensic laboratories worldwide for creating complete DNA profiles from low copy number template for comparison purposes along with its associated risks for forensic purposes